FORMULATION AND EFFECTIVENESS TEST OF ANTISEPTIC LIQUID HAND WASHING SOAP PREPARATION FROM TARO LEAF ETHANOL EXTRACT (Colocasia esculenta) - Elvita Nurwahdini; Nur Mahdi; Ani Agustina (Journal of Pharmacology Experiment and Pharmaceutical Technology, 2025)
The use of natural ingredients as active ingredients with antibacterial activity for making hand soap is still very little. The researcher is interested in conducting research on the formulation and effectiveness test of antiseptic liquid hand soap preparations from ethanol extract of taro leaves (Colocasia esculenta). The extraction process using 70% ethanol solvent at a ratio of 1:10 for 3x24 hours. Phytochemical screening tests were carried out by testing flavonoid compounds, alkaloids, saponins, tannins, and terpenoids. We prepared a Liquid Hand Washing Soap from Taro Leaf Extract (Colocasia esculenta) using a standard formula with three concentrations. Antiseptic Effectiveness Test of Liquid Hand Washing Soap. The method used is the zigzag method. The extraction results obtained were 21.10 grams or 14.06%. The results of the phytochemical screening test were only steroids that showed negative results. Preparation of liquid handwashing soap with concentrations of ethanol extract from taro leaves at 4%, 6%, and 78% can reduce the number of colonies by 30.9%, 51.9%, and 52.5%, respectively.